Penerapan Extreme Programming Untuk Merancang Aplikasi Kemahasiswaan Berbasis Android - Burham Isnanto; Ari Amir Alkodri; Supardi Supardi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Student activities reports are one of the standards assessed in submitting accreditation forms for study programs and faculties. Student data for 5 years must be recorded along with supporting evidence to be submitted and assessed by the assessor. This application was created using extreme programming and the React Native framework with input from the student affairs and quality assurance section. The testing process uses ISO 9126 with stakeholders and testing the effectiveness, efficiency, usefulness to ensure that the application can be used and fits the functional needs from the relevant sections. The research results are in the form of an application which contains menu of student data, student activity units, Atmaluhur alumni, activity proposals, student affairs agendas, tracer study results, and student achievements. This application, after being tested for the functional aspects, gets a value of 82.65% (good criteria), the reliability aspect is 84.03 (good criteria), the usability aspect is 87.20 (very good criteria), and the efficiency aspect is 80.40 (good criteria). ), so that the overall average is 83.57 (good criteria).